1997
DOI: 10.1177/0002764297040004011
|View full text |Cite
|
Sign up to set email alerts
|

The Social/Behavioral Construction of Employees as Strategic Actors on Company Boards of Directors

Abstract: In this article, the authors try to develop a theoretical frame of reference to help us understand the social construction of employees as strategic company actors on boards of directors. In 1973, the Danish Parliament passed an act granting employees the right to elect two members to sit on a company's board of directors. The authors attempt to understand the processes by which employee representatives infused this institutional form with meaning through a process of identity construction. This construction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Partnership has been promoted by unions (Triantafillou, 2003) and can be seen as an enterprise-level manifestation of the tradition for cooperation between trade unions and employers' associations (Hvid and Hasle, 2003;Kristensen, 2003). It has been suggested that employees in Scandinavian countries are more inclined to share responsibility with management than in other countries (Lindkvist and Llewellyn, 2003) and that the constructive attitude is seen as necessary to influence organizational change (Bicknell and Knudsen, 2006) and retain workplaces (Christensen and Westenholz, 1997;Westenholz, 2003). Partnerships between management and employee representatives are also seen as an outcome of the Danish works councils, sometimes labelled cooperation committees, that emerged in 1947 in an agreement between trade unions and employers' organizations with the aim of encouraging collaboration between management and employee representatives (see, for example, Knudsen, 1995;Westenholz, 2006).…”
Section: Danish Employee Relationsmentioning
confidence: 99%
“…Partnership has been promoted by unions (Triantafillou, 2003) and can be seen as an enterprise-level manifestation of the tradition for cooperation between trade unions and employers' associations (Hvid and Hasle, 2003;Kristensen, 2003). It has been suggested that employees in Scandinavian countries are more inclined to share responsibility with management than in other countries (Lindkvist and Llewellyn, 2003) and that the constructive attitude is seen as necessary to influence organizational change (Bicknell and Knudsen, 2006) and retain workplaces (Christensen and Westenholz, 1997;Westenholz, 2003). Partnerships between management and employee representatives are also seen as an outcome of the Danish works councils, sometimes labelled cooperation committees, that emerged in 1947 in an agreement between trade unions and employers' organizations with the aim of encouraging collaboration between management and employee representatives (see, for example, Knudsen, 1995;Westenholz, 2006).…”
Section: Danish Employee Relationsmentioning
confidence: 99%
“…Denmark has developed a system of codetermination granting employees the right to discuss matters of mutual importance with management through their shop stewards and as employee members of the company board (Christensen and Westenholz, 1997). In 1973, the Danish parliament passed an act granting employees in private enterprises with more than 50 employees 2 the right to elect every second year 3 two representatives 4 to sit on the company's board of directors.…”
Section: Industrial Relationsmentioning
confidence: 99%
“…Today 75% of Danish ®rms with more than 200 employees have employee representatives on their boards. Both unions and employers' associations offer courses introducing the employee representatives to strategy, management, ®nancial control and corporate legislation (Christensen and Westenholz, 1997).…”
Section: Industrial Relationsmentioning
confidence: 99%
“…However, by understanding institutions as independent variables New Institutional theory became unable to explain organizational change. A number of researchers have since attempted to develop a New Institutional theory capable of explaining organizational change as the outcome of the role that institutional entrepreneurs play in the development (Borum and Westenholz, 1995;Boxenbaum and Battilana, 2004;Brint and Karabel, 1991;Christensen and Westenholz, 1997;DiMaggio, 1988;Fligstein, 1997;Friedland and Alford, 1991;Greenwood and Hinings, 2002,;Oliver, 1991;Scott, 1995;Seo and Creed, 2002;Tolbert and Zucker, 1983). In the paper, I elaborate these ideas by combining the theory of institutional entrepreneurs with discourse theory.…”
Section: Introductionmentioning
confidence: 99%